The growing pipeline of natural aminoacyl-tRNA synthetase inhibitors for malaria treatment. Issue 2 (2nd April 2016) - Saint-Léger, Adélaïde; Sinadinos, Christopher; Ribas de Pouplana, Lluís
ABSTRACT: Malaria remains a major global health problem. Parasite resistance to existing drugs makes development of new antimalarials an urgency. The protein synthesis machinery is an excellent target for the development of new anti-infectives, and aminoacyl-tRNA synthetases (aaRS) have been validated as antimalarial drug targets. However, avoiding the emergence of drug resistance and improving selectivity to target aaRS in apicomplexan parasites, such as Plasmodium falciparum, remain crucial challenges. Here we discuss such issues using examples of known inhibitors of P. falciparum aaRS, namely halofuginone, cladosporin and borrelidin (inhibitors of ProRS, LysRS and ThrRS, respectively). Encouraging recent results provide useful guidelines to facilitate the development of novel drug candidates which are more potent and selective against these essential enzymes.